Stimulating Factors and Origins of Precursor Cells in Traumatic Heterotopic Ossification Around the Temporomandibular Joint in Mice - Zhao, Yan; Ouyang, Ningjuan; Chen, Long; Zhao, Hanjiang; Shen, Guofang; Dai, Jiewen (Frontiers in Cell and Developmental Biology, 2020)
The contributing factors and the origins of precursor cells in traumatic heterotopic ossification around the temporomandibular joint (THO-TMJ), which causes obvious restriction of mouth opening and maxillofacial malformation, remain unclear. In this study, our findings demonstrated that injured chondrocytes in the condylar cartilage, but not osteoblasts in the injured subchondral bone, played definite roles in the development of THO-TMJ in mice. Injured condylar chondrocytes without articular disc reserves might secrete growth factors, such as IGF1 and TGFβ2, that stimulate precursor cells, such as endothelial cells and muscle-derived cells, to differentiate into chondrocytes or osteoblasts and induce THO-TMJ. Preserved articular discs can alleviate the pressure on the injured cartilage and inhibit the development of THO-TMJ by inhibiting the secretion of these growth factors from injured chondrocytes. However, the exact molecular relationships among trauma, the injured condylar cartilage, growth factors such as TGFβ2 and pressure need to be explored in detail in the future.